Let there be bioluminescence: development of a biophotonic imaging platform for in situ analyses of oral biofilms in animal models. (5th August 2015) - Merritt, Justin; Senpuku, Hidenobu; Kreth, Jens
Summary: In the current study, we describe a novel biophotonic imaging‐based reporter system that is particularly useful for the study of virulence in polymicrobial infections and interspecies interactions within animal models. A suite of luciferase enzymes was compared using three early colonizing species of the human oral flora ( S treptococcus mutans, S treptococcus gordonii and S treptococcus sanguinis ) to determine the utility of the different reporters for multiplexed imaging studies in vivo . Using the multiplex approach, we were able to track individual species within a dual‐species oral infection model in mice with both temporal and spatial resolution. We also demonstrate how biophotonic imaging of multiplexed luciferase reporters could be adapted for real‐time quantification of bacterial gene expression in situ . By creating an inducible dual‐luciferase expressing reporter strain of S . mutans, we were able to exogenously control and measure expression of nlm AB (encoding the bacteriocin mutacin IV) within mice to assess its importance for the persistence ability of S . mutans in the oral cavity. The imaging system described in the current study circumvents many of the inherent limitations of current animal model systems, which should now make it feasible to test hypotheses that were previously impractical to model.